Trigonometric approximation of functions in generalized Lebesgue spaces with variable exponent - Akgün, R. (Український математичний журнал, 2011)
We investigate the approximation properties of the trigonometric system in Lp(·)2π. We consider the fractional order moduli of smoothness and obtain direct, converse approximation theorems together with a constructive characterization of a Lipschitz-type class. Досліджено властивості наближення тригонометричної системи в Lp(⋅)2π. Розглянуто модулі гладкості дробового порядку та отримано пряму і обернену теореми наближення разом із конструктивною характеризацією класу типу Ліпшиця.